2008
DOI: 10.1097/inf.0b013e318150666d
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dengue Nonstructural Protein 1 Antigen for the Early Diagnosis During the Febrile Stage in Patients With Dengue Infection

Abstract: Dengue NS1 antigen testing is suggested as a helpful tool for the early diagnosis of dengue infection after the onset of fever. The additional Ig M antibody determination increased the diagnostic rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
47
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 14 publications
11
47
0
2
Order By: Relevance
“…This assay provides additional dengue diagnostic tool to the existing approaches of PCR, antibody capture ELISA and virus isolation 5,6,10,12,13,20,24,25,28 . Even though NS1 is a sensitive methodology for the detection of DENV it should never be used as the only methodology for DENV detection because it doesn't identify different serotypes 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This assay provides additional dengue diagnostic tool to the existing approaches of PCR, antibody capture ELISA and virus isolation 5,6,10,12,13,20,24,25,28 . Even though NS1 is a sensitive methodology for the detection of DENV it should never be used as the only methodology for DENV detection because it doesn't identify different serotypes 39 .…”
Section: Discussionmentioning
confidence: 99%
“…21,22,28,29 In the present study, we provide serological evidence that all infected patients were secondary dengue cases, which could be expected, because dengue infection is endemic in Vietnam. Nevertheless, contrary to previous studies, 27,30,31 our results suggest that the sensitivity of NS1 detection assays is not significantly affected by the immune status of the patient, which is in agreement with a previous work by Castro-Jorge and others.…”
Section: Discussionmentioning
confidence: 75%
“…These results are consistent with studies performed on venous samples during the same phase of dengue disease. [6][7][8][21][22][23][24] Second, we show here that this technique also exhibits a good sensitivity (92.3%) with capillary samples collected during the early convalescent phase of the disease. Although some studies have already reported the possibility of detecting the viral protein NS1 in venous samples after the acute phase of the disease, the sensitivities were lower than those sensitivities reported with capillary blood samples.…”
Section: Discussionmentioning
confidence: 89%
“…13,14 NS1 tests are also reported to be less sensitive in secondary dengue. 3,12,15 Little is known about the causes of false-positive NS1 tests, except for possible cross-reactivity with other flaviviruses and possibly, cytomegalovirus (CMV). 11,16 The two patients were not exposed to other flaviviruses, but they were not tested for CMV.…”
Section: Commentmentioning
confidence: 99%